In Vivo Gene Editing of Muscle Stem Cells with Adeno-Associated Viral Vectors in a Mouse Model of Duchenne Muscular Dystrophy - Jennifer B. Kwon; Adarsh R. Ettyreddy; Ashish Vankara; Joel D. Bohning; Garth Devlin; Stephen D. Hauschka; Aravind Asokan; Charles A. Gersbach (Molecular Therapy: Methods & Clinical Development, 2020)
Delivery of therapeutic transgenes with adeno-associated viral (AAV) vectors for treatment of myopathies has yielded encouraging results in animal models and early clinical studies. Although certain AAV serotypes efficiently target muscle fibers, transduction of the muscle stem cells, also known as satellite cells, is less studied. Here, we used a Pax7nGFP;Ai9 dual reporter mouse to quantify AAV transduction events in satellite cells. We assessed a panel of AAV serotypes for satellite cell tropism in the mdx mouse model of Duchenne muscular dystrophy and observed the highest satellite cell labeling with AAV9 following local or systemic administration. Subsequently, we used AAV9 to interrogate CRISPR/Cas9-mediated gene editing of satellite cells in the Pax7nGFP;mdx mouse. We quantified the level of gene editing using a Tn5 transposon-based method for unbiased sequencing of editing outcomes at the Dmd locus. We also found that muscle-specific promoters can drive transgene expression and gene editing in satellite cells. Lastly, to demonstrate the functionality of satellite cells edited at the Dmd locus by CRISPR in vivo, we performed a transplantation experiment and observed increased dystrophin-positive fibers in the recipient mouse. Collectively, our results confirm that satellite cells are transduced by AAV and can undergo gene editing to restore the dystrophin reading frame in the mdx mouse.